2015
DOI: 10.33751/jf.v5i2.410
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Senyawa Bullatalisin Sebagai Inhibitor Protein Leukotrien A4 Hidrolase Pada Kanker Kolon Secara in Silico

Abstract: ABSTRAK Kanker kolon merupakan jenis kanker yang dapat menyebabkan kematian. Salah satu penyebabnya adalah pertumbuhan Leukotrien A4 hidrolase yang tidak terkontrol. Leukotrien A4 hidrolase dapat dijadikan target terapi dalam menekan pertumbuhan sel kanker. Bullatalisin merupakan senyawa turunan asetogenin yang memiliki potensi inhibitor terhadap Leukotrien A4 hidrolase. Penelitian ini bertujuan menentukan potensi Bullatalisin sebagai inhibitor secara in silico berdasarkan energi bebas Gibbs (?G), tetapan inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
7
0
3
Order By: Relevance
“…From the native ligand redocking test on 3OLS protein, it was found that the root mean deviation (RMSD) <2. The RMSD value <2 indicates that the software for the molecular docking process is good and can be used for the docking of compounds in 3OLS proteins (Noviardi and Fachrurrazie, 2015;Pinto et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…From the native ligand redocking test on 3OLS protein, it was found that the root mean deviation (RMSD) <2. The RMSD value <2 indicates that the software for the molecular docking process is good and can be used for the docking of compounds in 3OLS proteins (Noviardi and Fachrurrazie, 2015;Pinto et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The in silico study of quercetin with caspase 3 and COX-2 proteins revealed the binding energy were -9.54 kcal/mol and kcal/mol [13]. Another study showed the in silico study of bullatalicin to LTA4H (PDB ID: 3U9W) with grid sizes x = 60 Å, y = 60 Å, and z = 60 Å produced Gibbs free energy of -11.80 kcal/mol, while 28P native ligand -11.30 kcal/mol [14]. Other compounds derived from Lycopersicon esculentum such as chlorogenic acid, gallic acid, protocatechuic acid, quercetin, and vanillic acid showed inhibitory activity against beta-catenin associated with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RMSD (Root Mean Squared Deviation) menunjukkan penyimpangan pose ligan antara struktur kristalografi dengan struktur hasil re-docking. Fleksibilitas ligan dapat mempengaruhi ketepatan posisi kompleks yang terbentuk [13]. Nilai RMSD yang mendekati nol menunjukkan kesesuaian pose ligan hasil penambatan ulang yang mirip dengan konformasi kristalografi.…”
Section: Hasil Dan Pembahasanunclassified